2017
DOI: 10.3389/fendo.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence of Epigenetic Modifications in Vascular Complication of Diabetes

Abstract: Genes, dietary, and lifestyle factors have been shown to be important in the pathophysiology of diabetes and associated microvascular complications. Epigenetic modifications, such as DNA methylation, histone acetylation, and post-transcriptional RNA regulation, are being increasingly recognized as important mediators of the complex interplay between genes and the environment. Recent studies suggest that diabetes-induced dysregulation of epigenetic mechanisms resulting in altered gene expression in target cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 120 publications
(149 reference statements)
1
41
0
Order By: Relevance
“…Diabetic hyperglycemic alterations of blood vessel viability and integrity lead to multi-organ dysfunction that results in endothelial dysfunction linked to epigenetic remodeling 17 (e.g., DNA methylation 51 , histone marks 52,53 , and oxidative stress 54,55 ). Several studies have shown that these aberrant epigenetic changes may be partially overcome by genome-wide chemical treatments that restore some endothelial function 56,57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic hyperglycemic alterations of blood vessel viability and integrity lead to multi-organ dysfunction that results in endothelial dysfunction linked to epigenetic remodeling 17 (e.g., DNA methylation 51 , histone marks 52,53 , and oxidative stress 54,55 ). Several studies have shown that these aberrant epigenetic changes may be partially overcome by genome-wide chemical treatments that restore some endothelial function 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional hiPSC adopt a spectrum of mEpiSC-like pluripotent states with highly variable lineage-primed gene expressions and post-implantation primed epiblast epigenetic marks that result in inconsistent or diminished interline differentiation potencies 12,13 . Moreover, epigenetic aberrations in diseased states such as diabetes further inhibit efficient donor cell reprogramming to functional pluripotent states [14][15][16][17][18] .…”
mentioning
confidence: 99%
“…In this disease, the renin-angiotensin system also has a crucial role as it also leads to damage to neuronal vascular cells and retina [77]. Diabetes induces epigenetic changes (DNA methylation, histone acetylation and post-transcriptional RNA regulation) that lead to altered gene expression (genes involved in oxidation, angiogenesis, extracellular matrix degradation), which modifies the function of retinal vascular cells that are crucial in DR [78,79]. Through the analysis of in vitro and in vivo studies, several characteristics of inflammation have been detailed, such as leukostasis, neutrophil and macrophage infiltration, complement and microglial induction, positive regulation of cytokines, as well as blood flow expansion, vascular permeability and tissue edema [3].…”
Section: Diabetic Retinopathy Angiogenesis and Anti-angiogenic Therapymentioning
confidence: 99%
“…Epigenetic mechanisms, such as DNA methylation, histone post‐translational modifications in chromatin and non‐coding RNAs, mediate the interplay between genetic and environmental risk factors. Persistence of epigenetic changes might contribute to the metabolic memory phenomenon and to the oxidative stress, inflammation and extracellular matrix accumulation, all of which lead to the development of DR …”
Section: Introductionmentioning
confidence: 99%
“…1,4 Epigenetic mechanisms, such as DNA methylation, histone post-translational modifications in chromatin and non-coding RNAs, mediate the interplay between genetic and environmental risk factors. Persistence of epigenetic changes might contribute to the metabolic memory phenomenon and to the oxidative stress, inflammation and extracellular matrix accumulation, 5,6 all of which lead to the development of DR. 5 In this context, several studies have reported abnormal expression of microRNAs (miRNAs/miRs) in retinal cells under hyperglycemic conditions and in murine models of DR. [7][8][9] MiRNAs are small endogenous non-coding RNAs that in general silence gene expression at the posttranscriptional level by pairing to specific sequences in the 3'-untranslated region of their target mRNAs, thereby repressing protein synthesis. MiRNAs regulate cell development and function by modulating the acquisition and maintenance of beta-cell identity, 10 cell growth, proliferation, differentiation, apoptosis and metabolism.…”
Section: Introductionmentioning
confidence: 99%